Let's explore Saturn - Orme, Helen; Orme, David, 1948 Mar. 1- (Tunbridge Wells, Kent : Ticktock Entertainment, 2007)
Photographs, illustrations, and simple text provide details about Saturn including what it looks like, its orbit, moons, and rings, and missions to explore the surface of the planet.
Where is Saturn? -- Planet facts -- The weather on Saturn -- Saturn's amazing rings -- Saturn's amazing Moon -- Saturn's biggest Moon -- Saturn in history -- What can we see? -- Missions to Saturn -- Future missions.
Includes index.
Library Media Connection.
3-6.
Keywords: Saturn (Planet) -- Juvenile literature; Saturn (Planet); Saturn (Planet)